Upaya Untuk Meningkatkan Hasil Belajar Siswa Dalam Matematika Materi Pecahan Dengan Menggunakan Alat Peraga Benda Konkret Di Kelas III SDN Pinang 5 Kota Tangerang - Iin Inayah; Edi Cahyadinata (Algebra: Journal of Matematics, Statistics and Computation, 2024)
The problem with this research is the poor student learning outcomes and the lack of teachers using visual aids. This study seeks to improve the learning outcomes of class III students at SDN Pinang 5 Tangerang City studying mathematics using teaching aids that focus on concrete objects. This study includes an action study in class, conducted on students at SDN Pinang 5 class III. Research II was carried out in two cycles. Planning, explaining, practicing, and reflecting on action are the four steps in each cycle. After this research was conducted, the following findings were produced. Student learning outcomes are getting better. after the teacher uses concrete object props; This was proven in the first cycle with 32 students who had a score below 70 and 20 students with a score of more than 70 in the 12th completion and the level of students who achieved a score of more than 70 increased in the second cycle to 31 students with a score of more than 70 (96.875) . In conclusion, the use of a method that uses concrete object props can improve the mathematical abilities of class III students at SDN Pinang 5 on the subject of fractions.